Microencapsulação da microalga spirulina platensis e utilização no desenvolvimento de sorvete - Mortari, Letícia Moreira (2018)
Prevention of various pathologies through the use of antioxidant compounds is increasingly being sought by individuals who are interested in promoting health and well-being. Oxidative stress is known to increase the incidence of cancer and other degenerative diseases. Spirulina platensis is a microalgae known to have functional activity and potential to contribute to improving the health of its consumers. The antioxidants present in Spirulina microalgae may undergo changes in their stability, according to storage conditions. When added to food products, it may also have decreased stability depending on interactions with food components. The antioxidant compounds need to be active and bioavailable when ingested, and there is a need for technologies that allow the protection of natural antioxidants, aiming to increase their stability. Microencapsulation is one of the technologies capable of prote cting antioxidants from different conditions to which they can be exposed and, in addition, mask unpleasant taste and odor, making food more attractive to the consumer. The objective of this study was to evaluate whether the microencapsulation of Spirulina microalgae increases the stability of the antioxidant potential of the capsules at low temperatures, and whether microencapsulation affects the acceptability of added sorbets of the microalga. Spirulina was microencapsulated using 20DE maltodextrin and gum arabic, separately, using spray-dryer. After encapsulation, the characterization of the microcapsules was carried out and stability tests of the antioxidant potential in Spirulina powder and Spirulina encapsulated in freezing temperatures (-20ºC), refrigeration (4ºC) and ambient (25ºC) were performed. The antioxidant potential of the aqueous extract of the powdered and encapsulated microalgae, extracted from appropriate methodologies for each sample, was determined by the ABTS method. Spirulinaand Spirulina microencapsulated ice cream were developed in gum arabic and maltodextrin. The ice cream was characterized physicochemically and submitted to the sensorial evaluation of acceptability and sensorial attributes through CATA methodology. The Spirulina encapsulation process was successfully performed with high encapsulation efficiencies in gum arabic (85%) and maltodextrin (89%), obtaining homogeneous microcapsules with a mean size of 6.24 μm (maltodextrin) and 3.44 μm (gum arabic). The microencapsulation of Spirulina allows a slight protection of the antioxidant potential of the microalga at temperatures from 4ºC to 25ºC. There is a loss of about 70% of the antioxidant potential aft er 7 days at room temperature for Spirulina powder, and about 66% and 70% of the powders encapsulated in gum arabic and maltodextrin, respectively. The protection of the antioxidant potential occurs in storage of both microcapsules and Spirulina powder only in freezing temperatures. The added Spirulina ice cream showed a gain in protein content in relation to the standard formulation of 35%, 42% and 53% for the formulations of Spirulina ice cream in maltodextrin, Spirulina in gum arabic and pure Spirulina, respectively. All the ice cream formulations showed an acceptability index of 70% and an average purchase intention of 76.5%. The CATA test allowed to conclude that the encapsulation masks the taste of algae and algae aroma, however this fact does not lead to a greater acceptability of the samples where the microalga was encapsulated. The addition of Spirulina in ice cream can be performed without microencapsulation with gain in the protein content and without prejudice to the antioxidant potential and the acceptability.